The Influence of Democratic Parenting Styles on Early Childhood Independence in Facing Challenges in The Era of Society 5.0 - Salsa Ainurrahmah; Asep Kurnia Jayadinata; Gia Nikawanti; Deany Yasir Wirya (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
The research was driven by concerns that many young children in Indonesia still depend on adults for routine tasks, which may limit the development of essential self-help skills needed for successful adaptation to formal schooling. This study aims to examine the influence of democratic parenting styles on early childhood independence in facing challenges in the era of Society 5.0. Using a quantitative survey approach, data were collected from parents who applied democratic parenting, using a 1–4 Likert-scale questionnaire. The Pearson correlation test showed a significance value of 0.031 < 0.05, indicating a positive and significant relationship between democratic parenting and early childhood independence. These findings suggest that democratic parenting can effectively enhance children’s confidence, responsibility, and autonomy, supporting their ability to adapt to the demands of Society 5.0.